Centro gastronómico (La Mariscal - El Ejido) - Vera Mena, Kevin Patricio (2018)
Urban Parish La Mariscal, belonging to the province of Pichincha, inside Ecuadorian Highlands Region, is nationally known for being a strategic point where commercial activity predominates. However, there are countless conflicts that have affected the users that living in the study area. The workshop ARO - 960 (2017-2) draws up an Urban Ordering Plan, which allows the understanding of the problems inside the city due to its physical space, urban dynamics, conflicts, potentialities and possible solutions; reflecting them in a well-defined urban plan with a vision for the future. The Gastronomic Center (La Mariscal - El Ejido) is born from that vision; mainly, promoting equipment that improves the living conditions of its inhabitants and visitors. The current degree paper work focuses in the search of connecting and integrating the equipment inside an urban-natural area, respecting and valuing the natural physical components, present in the intervention area.